2009
DOI: 10.1098/rstb.2009.0015
|View full text |Cite
|
Sign up to set email alerts
|

Pre-semantically defined temporal windows for cognitive processing

Abstract: Neuronal oscillations of different frequencies are hypothesized to be basic for temporal perception; this theoretical concept provides the frame to discuss two temporal mechanisms that are thought to be essential for cognitive processing. One such mechanism operates with periods of oscillations in the range of some tens of milliseconds, and is used for complexity reduction of temporally and spatially distributed neuronal activities. Experimental evidence comes from studies on temporal-order threshold, choice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
219
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 181 publications
(233 citation statements)
references
References 80 publications
8
219
1
5
Order By: Relevance
“…The periodicity of mental activity was documented by Pöppel and others in a series of psychophysical studies (Schleidt, Eibl-Eibesfeldt, & Pöppel, 1987; for recent review, see Pöppel, 2009)Temporal segmentation of human activity is observed in a series of daily living activities, such as gesture-making, perception, poetry, and music (Haase et al, 1997). A role for oscillatory neural activity in building psychologically relevant neuronal assemblies has been emphasized by Singer (1993;Fries, Nikolic, & Singer, 2007) in a series of neurophysiological studies conducted over the past 20 years.…”
Section: The Functional Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The periodicity of mental activity was documented by Pöppel and others in a series of psychophysical studies (Schleidt, Eibl-Eibesfeldt, & Pöppel, 1987; for recent review, see Pöppel, 2009)Temporal segmentation of human activity is observed in a series of daily living activities, such as gesture-making, perception, poetry, and music (Haase et al, 1997). A role for oscillatory neural activity in building psychologically relevant neuronal assemblies has been emphasized by Singer (1993;Fries, Nikolic, & Singer, 2007) in a series of neurophysiological studies conducted over the past 20 years.…”
Section: The Functional Modelmentioning
confidence: 99%
“…The second formal function is the temporal organization of operations in the system, which can be called chronometric or synchronized timing. From a series of psychophysical studies, Pöppel (1993Pöppel ( , 2009 proposed that mental activity is organized periodically and that the pacemaker results from the oscillatory nature of neuronal activity, with information reverberating in cortico-subcortico-cortical loops. Mental events that occur in the synchronization of oscillatory neuronal phenomena, which has an upper limit of a few seconds, correspond to the so-called psychological moment of classical authors (James, 1890).…”
Section: The Functional Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in visual and auditory perception in humans the transduction of the acoustic information is much shorter then the visual [30]. In it is suggested that in humans a temporal window with the duration of 3 s is created [15]. This window represents the psychological concept of "now" [29].…”
Section: Biological Principle Of Energy Minimizationmentioning
confidence: 99%
“…It is preformed subconsciously by our brain as a coherent explanation of events in a temporal window [15]. Events with higher surprise are more difficult to explain and require more energy.…”
Section: Introductionmentioning
confidence: 99%